2003
DOI: 10.1258/00222150360600850
|View full text |Cite
|
Sign up to set email alerts
|

Otoacoustic emissions in patients with hypotension

Abstract: The aim of this study was to investigate the relation between hypotension and slowly developing hearing impairment, using otoacoustic emissions. A group of 42 patients was examined, with diastolic blood pressure < or = 60 mmHg and systolic blood pressure < or = 105 mmHg. The subjects underwent biochemical, cardiological, ENT and audiological examinations. Distortion product otoacoustic emissions (DPOAE) were recorded in the format of DP-gram. The results were compared to the data of 30 normal persons of simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…It has been reported on several occasions that OAEs may be a more sensitive test of cochlear function than puretone audiometry (PTA) in indicating subclinical cochlear damage. [9][10][11][12] Although both transiently evoked and distortion product OAEs (DPOAEs) have been used in studying the effect of noise on the cochlea, [13][14] the latter are probably the most useful. It has been found that DPOAEs arise from localized sources along the cochlea, thus providing frequency specific information, and are quite stable in level.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported on several occasions that OAEs may be a more sensitive test of cochlear function than puretone audiometry (PTA) in indicating subclinical cochlear damage. [9][10][11][12] Although both transiently evoked and distortion product OAEs (DPOAEs) have been used in studying the effect of noise on the cochlea, [13][14] the latter are probably the most useful. It has been found that DPOAEs arise from localized sources along the cochlea, thus providing frequency specific information, and are quite stable in level.…”
Section: Introductionmentioning
confidence: 99%
“…15 More generally, audiological studies in people with hypotension showed a mild hearing impairment (especially with low frequencies) in a large number of cases compared to control groups. 16,17 The importance of autonomic dysfunction in generating peripheral vertigo and possibly involving cochlear symptoms, however, thus creating a labyrinthine imbalance, has 18 and the same trigger has for a long time been considered to play a role in the pathophysiology of Ménière's disease. 19,20 In fact, it seems reasonable to assume that a factor which is likely to have an influence on the posterior labyrinth may extend its action even into the cochlear partition of this end-organ.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed the vascular risk-free population has been extensively studied over the last years and the possibility of a cochlear damage as SHL in young and healthy subjects with low blood pressure values was demonstrated: in such cases, an abrupt lowering of blood pressure followed by an abnormal vasoconstriction could be responsible for the damage [3][4][5]; the same model subsequently permitted to draw a hemodynamic profile of subjects possibly more prone to some kind of inner ear ''idiopathic'' imbalance [6], and to outline a link between a transiently insufficient peripheral perfusion of systemic origin and an acute inner ear sufferance both in subjects submitted to an aggressive anti-hypertensive therapy [7] and in subjects with severe heart failure [8]. Briefly, the possibility of an inner ear abrupt damage deriving from dysfunctional causes rather than an underlying organic disorder has been widely elucidated in the last 15 years and has found a series of confirmations over the time: accordingly, among the numerous causative factors that must be considered as responsible for SHL it is widely reminded in the literature [9][10][11][12][13][14][15][16]. When considering that even systemic hemodynamic changes can play a crucial role in the labyrinthine homeostasis, it is possible to yield an exhaustive scenario of the complex considered problem and, in some cases at least, to widen the horizon and more easily plan an effective therapeutic strategy.…”
mentioning
confidence: 99%